THE TRANSLATION OF INDONESIAN PASSIVE VOICE INTO ENGLISH IN THE NOVEL 9 SUMMERS 10 AUTUMNS TRANSLATED BY MAGGIE TJIOJAKIN - Desi Amalia; Andang Saehu; Irman Nurhapitudin (CALL, 2019)
The study is conducted based on qualitative research design with descriptive analysis. The data are 67 passive construction in Indonesian and English as used in the novel “9 Summers 10 Autumns (Dari Kota Apel ke The Big Apple)” and translated into “9 Summers 10 Autumns (From the City of Apples to the Big Apple). The research problems are the first what are the corresponding equivalents of Indonesian passive in English as used in the Novel 9 Summers 10 Autumns and its translation, the second what is the translation method or procedure that used in the process of passive voice translation. The steps and procedures of discovering the answer to the both of research problems are shown under the discussion of research method which includes: (1) the data source, (2) method and technique of collecting the data consisting of observation method and note-taking technique; (3) method and technique of analyzing the data. The results of the study show that among the passive in Indonesian which can be identified in SL, most are marked by prefix di- (prefix di- + verb base) and (prefix di-+ verb base + suffix –kan, -i) which are also translated into passive in English (be+past participle ) with four types namely to infinitive translation, by agent translation (stated and implied) and the rest translated into active. This clearly reveals that some passives in SL are retained, namely translated into passive in English and some others are translated into actives. Second, from the whole data analysis the researcher found 4 types of translation methods or procedures used in the passive translation, namely literal translation, transposition, modulation, and adaptation.Keywords: Passive voice, translation procedures, novel